Temperature and Pressure Measurements and Visualization of He II Cavitation Flow through Venturi Channel - Ishii, T; Murakami, M; Harada, K (AIP conference proceedings, 2004)
He II cavitation flow through a Venturi channel was experimentally investigated through temperature and pressure measurements and optical visualization. So far some distinctive features of cavitation between He II and He I flows were clarified. Then, detailed measurements were added for further investigation, such as the measurements of the temperature drop distribution throughout the flow channel and the void fraction. Further considerations were given on the cavitation inception with emphasis on the superheat ingof liquid helium, and the effect of the flow separation on cavitation.